On‐Chip Chemical Synthesis Using One‐Step 3D Printed Polyperfluoropolyether. Issue 7 (25th April 2022) - Goralczyk, Andreas; Mayoussi, Fadoua; Sanjaya, Mario; Corredor, Santiago Franco; Bhagwat, Sagar; Song, Qingchuan; Schwenteck, Sarah; Warmbold, Andreas; Pezeshkpour, Pegah; Rapp, Bastian E.
Abstract: Three‐dimensional (3D) printing has already shown its high relevance for the fabrication of microfluidic devices in terms of precision manufacturing cycles and a wider range of materials. 3D‐printable transparent fluoropolymers are highly sought after due to their high chemical and thermal resistance. Here, we present a simple one‐step fabrication process via stereolithography of perfluoropolyether dimethacrylate. We demonstrate successfully printed microfluidic mixers with 800 µm circular channels for chemistry‐on‐chip applications. The printed chips show chemical, mechanical, and thermal resistance up to 200 °C, as well as high optical transparency. Aqueous and organic reactions are presented to demonstrate the wide potential of perfluoropolyether dimethacrylate for chemical synthesis. Abstract : We 3D‐printed microfluidic chips with 800 µm circular channels using stereolithography of perfluoropolyether dimethacrylate. Aqueous and organic reactions are monitored as the reaction of methylene blue with ascorbic acid by visual discoloration of the solution, and the synthesis of N‐benzylidenbenzylamin at ambient conditions by FTIR measurements.